2023
DOI: 10.3390/catal13020248
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Steam Reforming over La1-xSrxCeO3-δ Catalysts for Hydrogen Production: Optimization of Operating Parameters

Abstract: In this study, a series of A-site strontium-doped La1-xSrxCeO3-δ (x = 0.2, 0.4, 0.6, 0.8) perovskite catalysts were synthesized via the ethylenediaminetetraacetic acid (EDTA) sol-gel method for hydrogen production by methanol steam reforming. The fresh and the reduced catalysts are characterized by scanning X-ray (XRD), energy dispersive X-ray spectroscopy (EDS) and scanning electron microscopy (SEM) techniques. Results showed that La0.6Sr0.4CeO3-δ exhibited the best performance among the La1-xSrxCeO3-δ cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The results evidenced a remarkable catalytic activity due to the stability of Co particles, which were highly dispersed in their reduced state. Similarly, Chen et al recently reported a series of A-site Sr-doped La 1– x Sr x CeO 3−δ ( x = 0.2, 0.4, 0.6, 0.8) perovskite catalysts for H 2 production by SRM, showing that La 0.6 Sr 0.4 CeO 3−δ exhibited the best performance at optimal reaction conditions. In summary, Sr-substituted lanthanum–cobalt oxide perovskites may be potential catalytic precursors for the SRM and OSRM processes to supply H 2 -rich gas for SOFC applications.…”
Section: Introductionmentioning
confidence: 80%
“…The results evidenced a remarkable catalytic activity due to the stability of Co particles, which were highly dispersed in their reduced state. Similarly, Chen et al recently reported a series of A-site Sr-doped La 1– x Sr x CeO 3−δ ( x = 0.2, 0.4, 0.6, 0.8) perovskite catalysts for H 2 production by SRM, showing that La 0.6 Sr 0.4 CeO 3−δ exhibited the best performance at optimal reaction conditions. In summary, Sr-substituted lanthanum–cobalt oxide perovskites may be potential catalytic precursors for the SRM and OSRM processes to supply H 2 -rich gas for SOFC applications.…”
Section: Introductionmentioning
confidence: 80%
“…However, it is expected that instability under high temperature reducing environments will be generally observed, and such materials should be considered as "perovskite-derived" catalysts. Nevertheless, Chen et al demonstrated that (La 0.6 Sr 0.4 )CeO 3-δ is stable toward 600 °C reduction under 10 vol % H 2 , 199 possibly reflecting the higher stability of (La 0.6 Sr 0.4 )CeO 3-δ cubic perovskites to reducing environments. 200 Gallego et al also investigated the stability of LaNiO 3 and LaFeO 3 perovskites under reducing environments at 900 °C, 201 noting that although the former decomposed to Ni/La 2 O 3 the latter was almost unchanged.…”
Section: Reveal the Formation Of Exsolved Ni Nps (Purple Circles)mentioning
confidence: 99%
“…However, it is expected that instability under high temperature reducing environments will be generally observed, and such materials should be considered as “perovskite-derived” catalysts. Nevertheless, Chen et al demonstrated that (La 0.6 Sr 0.4 )­CeO 3‑δ is stable toward 600 °C reduction under 10 vol % H 2 , possibly reflecting the higher stability of (La 0.6 Sr 0.4 )­CeO 3‑δ cubic perovskites to reducing environments . Gallego et al.…”
Section: Properties Of Perovskitesmentioning
confidence: 99%
“…Owing to the extremely important role of the support in the catalyst system, it can not only promote the dispersion of active components, but also suppress the sintering of active metals when there is a strong interaction between the support and metal. Among them, perovskite (ABO 3 ) supports are a widely used type of support [37][38][39]. Its A and B sites can be finely regulated and substituted, and it has very high sintering resistance, showing good application prospects in many fields [40].…”
Section: Introductionmentioning
confidence: 99%